Remote Controlled Laboratory as a Modern Form of Engineering Education - Župerl, Uroš; Ploj Virtič, Mateja (Revija za elementarno izobraževanje, 2013)
Technological development enables many benefits and improvements with regard to the educational process. This paper discusses the development of remote laboratory architecture for web-based programming and control of a passenger lift located at the Faculty of Mechanical Engineering, University of Maribor (UM FME). A dedicated web page provides users with the opportunity to learn how to programme and control a programmable logic controller (PLC) from remote sites. Remote-controlled experiments involving additional visual support have similar learning effects compared to practical work in a laboratory, the difference being that students acquire additional technological knowledge in the latter. This paper presents, among other things, the details regarding the development of the respective laboratory for remote control of lift operation. In conclusion, the article critically examines the advantages and disadvantages of the here presented remote-controlled laboratory.
Keywords: remote controlled laboratory; passenger lift; laboratory experimentation; mechanical engineering; undergraduate study